A reduction of prothrombin conversion by cardiac surgery with cardiopulmonary bypass shifts the haemostatic balance towards bleeding - Kremers, Romy M. W.; Bosch, Yvonne P. J.; Bloemen, Saartje; de Laat, Bas; Weerwind, Patrick W.; Mochtar, Bas; Maessen, Jos G.; Wagenvoord, Rob J.; Al Dieri, Raed; Coenraad Hemker, H. (Thrombosis and Haemostasis, 2016)
Cardiac surgery with cardiopulmonary bypass (CPB) is associated with blood loss and post-surgery thrombotic complications. The process of thrombin generation is disturbed during surgery with CPB because of haemodilution, coagulation factor consumption and heparin administration. We aimed to investigate the changes in thrombin generation during cardiac surgery and its underlying pro- and anticoagulant processes, and to explore the clinical consequences of these changes using in silico experimentation. Plasma was obtained from 29 patients undergoing surgery with CPB before heparinisation, after heparinisation, after haemodilution, and after protamine administration. Thrombin generation was measured and prothrombin conversion and thrombin inactivation were quantified. In silico experimentation was used to investigate the reaction of patients to the administration of procoagulant factors and/or anticoagulant factors. Surgery with CPB causes significant coagulation factor consumption and a reduction of thrombin generation. The total amount of prothrombin converted and the rate of prothrombin conversion decreased during surgery. As the surgery progressed, the relative contribution of α2-macroglobulin-dependent thrombin inhibition increased, at the expense of antithrombin-dependent inhibition. In silico restoration of post-surgical prothrombin conversion to pre-surgical levels increased thrombin generation excessively, whereas co-administration of antithrombin resulted in the normalisation of post-surgical thrombin generation. Thrombin generation is reduced during surgery with cardiopulmonary bypass because of a balance shift between prothrombin conversion and thrombin inactivation. According to in silico predictions of thrombin generation, this new balance increases the risk of thrombotic complications with prothrombin complex concentrate administration, but not if antithrombin is co-administered.
Keywords: Cardiopulmonary bypass; thrombin generation; thrombin inactivation; prothrombin conversion; transfusion